Low back pain in adolescent rowers: Association to muscle changes detected by magnetic resonance imaging - Marth, A. A.; Auer, T. A.; Bertalan, G.; Gebert, P.; Kirchenberger, T.; Geisel, D.; Hamm, B.; Keller, S. (Journal of Sports Sciences, 2023)
Adult elite rowers are at risk of developing low back pain (LBP). However, LBP data on adolescent elite rowers is currently insufficient. Therefore, the aim of this study was to assess LBP prevalence, LBP intensity and training characteristics in male adolescent elite rowers and a healthy control group. Twenty rowers (mean age 15.8 ± 1.2 years) and a non-athletic control group matched by age and gender (n = 13) were prospectively enrolled and underwent LBP assessment with a validated questionnaire and magnetic resonance imaging (MRI) of the lumbar spine muscles, which included a T2-mapping sequence. From the quantitative image data, T2 relaxation times were calculated. The prevalence of LBP in the last 24 hours and 3 months in the rowing group was 55.0% and 85.0%, respectively, compared to 23.1% and 30.8% in the control group (p < 0.001). Rowers had significantly longer T2 relaxation times of the paraspinal muscles compared to controls (p = 0.041). LBP intensity was associated with longer T2 relaxation times (p < 0.001). Adolescent rowers had a higher prevalence of LBP compared to an age-matched control group. The observed increase in T2 relaxation might be explained by muscle soreness due to strenuous exercise, which is correlated with short-term pain intensity.